Konsep Manajemen Dakwah dalam Al-Qur’an : Kajian terhadap Surat An-Nahl Ayat 125 - Ausy Alaya Ilmy; Adiba Syaidatun Nisa; Hasan Muslihat (Jurnal Riset Rumpun Agama dan Filsafat, 2025)
Surah An-Nahl verse 125, which reads "Invite (mankind) to the way of your Lord with wisdom and good instruction, and argue with them in the best way," is a strategic foundation for understanding the concept of da'wah management. This verse identifies three key elements: wisdom (hikmah), good instruction (mau'izhah hasanah), and arguing in the best way (mujadilah bil-lattif). This research analyzes these three elements in the context of tarbiyah methodology, and examines the relevance of this concept in modern da'wah practice. Furthermore, this research highlights how the principle of wisdom in da'wah, as explained in Surah An-Nahl verse 125, requires an operational elaboration so that da'is can effectively implement it in various da'wah activities, including tabligh. Tabligh, as a form of da'wah bil lisan, utilizes the ability to speak to convey da'wah material to the community with various techniques that are wise and in accordance with the principles of wisdom, with the aim of comprehensively understanding Islamic teachings.